2013
DOI: 10.3136/nskkk.60.541
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Health Benefits of Different Eras of Japanese Foods : Lipid and Carbohydrate Metabolism Focused Research

Abstract: Since the Japanese are known for their long life span, Japanese food has potential for health promotion. To identify the era of Japanese food that was beneficial to health, we investigated the health enhancing effects of Japanese foods from different eras, focusing on lipid and carbohydrate metabolic systems. Based on the National Nutrition Survey, representative one-week menus of Japanese foods from 2005, 1990, 1975 and 1960 were prepared, cooked, and powderized. Each mixture of Japanese food was given to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…In addition, a control (CO) group was fed with normal diet and a high‐fat diet (HFD) group was fed with Western diet containing 5% of the replaced material without addition of Natto or soybeans. Energy was calculated using the modified Atwater method (4 kcal of protein, 9 kcal of lipid, 4 kcal of carbohydrate per g) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a control (CO) group was fed with normal diet and a high‐fat diet (HFD) group was fed with Western diet containing 5% of the replaced material without addition of Natto or soybeans. Energy was calculated using the modified Atwater method (4 kcal of protein, 9 kcal of lipid, 4 kcal of carbohydrate per g) …”
Section: Methodsmentioning
confidence: 99%
“…As the Japanese diet has become more westernized in the past 50 years, the prevalence of lifestyle diseases has increased . Therefore, we also examined the contents of Japanese diets from different years to determine which was most effective for maintaining good health . The Japanese diet from 2005 was defined as the modern Japanese diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional composition fat, protein, moisture, ash, carbohydrate and energy of the prepared diets was determined to confirm the actual values Table 3 . Fat was measured by acid digestion; protein by a modified Dumas method Sumigraph NC analyzer NC-220 F; Sumika Chemical Analysis Service ; moisture by vacuum oven drying; ash by direct ashing; and carbohydrate by subtracting the fat, protein, moisture and ash contents from the total amount 8,19 . The energy content was calculated using modified Atwater factors 4, 9 and 4 kcal/g for protein, fat and carbohydrate, respectively 19 .…”
Section: Preparation Of Test Dietsmentioning
confidence: 99%
“…Therefore, the 1975 Japanese diet appears to limit accumulation of visceral fat and is the least likely to cause obesity among Japanese diets from different eras. In subsequent studies, the 1975 Japanese diet has been shown to have beneficial effects on diabetes, fatty liver, dementia and lifespan 8,10 .…”
Section: Introductionmentioning
confidence: 99%